Calculus - Larson, Ron.; Bruce H. Edwards (Belmont, California : Brooks/Cole Publishing Company, 2010)
Counter The Larson CALCULUS program has a long history of innovation in the calculus market. It has been widely praised by a generation of students and professors for its solid and effective pedagogy that addresses the needs of a broad range of teaching and learning styles and environments. Each title is just one component in a comprehensive calculus course program that carefully integrates and coordinates print, media, and technology products for successful teaching and learning.
Chapter P: Preparation for Calculus. P.1 Graphs and Models. P.2 Linear Models and Rates of Change. P.3 Functions and Their Graphs P.4 Fitting Models to Data. Chapter 1: Limits and Their Properties. 1.1 A Preview of Calculus. 1.2 Finding Limits Graphically and Numerically. 1.3 Evaluating Limits Analytically. 1.4 Continuity and One-Sided Limits. 1.5 Infinite Limits. Section Project: Graphs and Limits of Trigonometric Functions. Chapter 2: Differentiation. 2.1 The Derivative and the Tangent Line Problem. 2.2 Basic Differentiation Rules and Rates of Change. 2.3 The Product and Quotient Rules and Higher-Order Derivatives. 2.4 The Chain Rule. 2.5 Implicit Differentiation. Section Project: Optical Illusions. 2.6 Related Rates. Chapter 3: Applications of Differentiation. 3.1 Extrema on an Interval. 3.2 Rolle's Theorem and the Mean Value Theorem. 3.3 Increasing and Decreasing Functions and the First Derivative Test. Section Project: Rainbows. 3.4 Concavity and the Second Derivative Test. 3.5 Limits at Infinity. 3.6 A Summary of Curve Sketching. 3.7 Optimization Problems. Section Project: Connecticut River. 3.8 Newton's Method. 3.9 Differentials. Chapter 4: Integration. 4.1 Antiderivatives and Indefinite Integration. 4.2 Area. 4.3 Riemann Sums and Definite Integrals. 4.4 The Fundamental Theorem of Calculus. Section Project: Demonstrating the Fundamental Theorem. 4.5 Integration by Substitution. 4.6 Numerical Integration. Chapter 5: Logarithmic, Exponential, and Other Transcendental Functions. 5.1 The Natural Logarithmic Function: Differentiation. 5.2 The Natural Logarithmic Function: Integration. 5.3 Inverse Functions. 5.4 Exponential Functions: Differentiation and Integration. 5.5 Bases Other than e and Applications. Section Project: Using Graphing Utilities to Estimate Slope. 5.6 Inverse Trigonometric Functions: Differentiation. 5.7 Inverse Trigonometric Functions: Integration. 5.8 Hyperbolic Functions. Section Project: St. Louis Arch. Chapter 6: Differential Equations. 6.1 Slope Fields and Euler's Method. 6.2 Differential Equations: Growth and Decay. 6.3 Separation of Variables and the Logistic Equation. 6.4 First-Order Linear Differential Equations. Section Project: Weight Loss. Chapter 7: Applications of Integration. 7.1 Area of a Region Between Two Curves. 7.2 Volume: The Disk Method. 7.3 Volume: The Shell Method. Section Project: Saturn. 7.4 Arc Length and Surfaces of Revolution. 7.5 Work. Section Project: Tidal Energy. 7.6 Moments, Centers of Mass, and Centroids. 7.7 Fluid Pressure and Fluid Force. Chapter 8: Integration Techniques, L'Hopital's Rule, and Improper Integrals. 8.1 Basic Integration Rules. 8.2 Integration by Parts. 8.3 Trigonometric Integrals. Section Project: Power Lines. 8.4 Trigonometric Substitution. 8.5 Partial Fractions. 8.6 Integration by Tables and Other Integration Techniques. 8.7 Indeterminate Forms and L'Hopital's Rule. Chapter 9: Infinite Series. 9.1 Sequences. 9.2 Series and Convergence. Section Project: Cantor's Disappearing Table. 9.3 The Integral Test and p-Series. Section Project: The Harmonic Series. 9.4 Comparisons of Series. Section Project: Solera Method. 9.5 Alternating Series. 9.6 The Ratio and Root Tests. 9.7 Taylor Polynomials and Approximations. 9.8 Power Series. 9.9 Representation of Functions by Power Series. 9.10 Taylor and Maclaurin Series. Chapter 10: Conics, Parametric Equations, and Polar Coordinates. 10.1 Conics and Calculus. 10.2 Plane Curves and Parametric Equations. Section Project: Cycloids. 10.3 Parametric Equations and Calculus. 10.4 Polar Coordinates and Polar Graphs. Section Project: Anamorphic Art. 10.5 Area and Arc Length in Polar Coordinates. 10.6 Polar Equations of Conics and Kepler's Laws. Chapter 11: Vectors and the Geometry of Space. 11.1 Vectors in the Plane. 11.2 Space Coordinates and Vectors in Space. 11.3 The Dot Product of Two Vectors. 11.4 The Cross Product of Two Vectors in Space. 11.5 Lines and Planes in Space. Section Project: Distances in Space. 11.6 Surfaces in Space. 11.7 Cylindrical and Spherical Coordinates. Chapter 12: Vector-Valued Functions. 12.1 Vector-Valued Functions. Section Project: Witch of Agnesi. 12.2 Differentiation and Integration of Vector-Valued Functions. 12.3 Velocity and Acceleration. 12.4 Tangent Vectors and Normal Vectors. 12.5 Arc Length and Curvature. Chapter 13: Functions of Several Variables. 13.1 Introduction to Functions of Several Variables. 13.2 Limits and Continuity. 13.3 Partial Derivatives. Section Project: Moire Fringes. 13.4 Differentials. 13.5 Chain Rules for Functions of Several Variables. 13.6 Directional Derivatives and Gradients. 13.7 Tangent Planes and Normal Lines. Section Project: Wildflowers. 13.8 Extrema of Functions of Two Variables. 13.9 Applications of Extrema of Functions of Two Variables. Section Project: Building a Pipeline. 13.10 Lagrange Multipliers. Chapter 14: Multiple Integration. 14.1 Iterated Integrals and Area in the Plane. 14.2 Double Integrals and Volume. 14.3 Change of Variables: Polar Coordinates. 14.4 Center of Mass and Moments of Inertia. Section Project: Center of Pressure on a Sail. 14.5 Surface Area. Section Project: Capillary Action. 14.6 Triple Integrals and Applications. 14.7 Triple Integrals in Cylindrical and Spherical Coordinates. Section Project: Wrinkled and Bumpy Spheres. 14.8 Change of Variables: Jacobians. Chapter 15: Vector Analysis. 15.1 Vector Fields. 15.2 Line Integrals. 15.3 Conservative Vector Fields and Independence of Path. 15.4 Green's Theorem. Section Project: Hyperbolic and Trigonometric Functions. 15.5 Parametric Surfaces. 15.6 Surface Integrals. Section Project: Hyperboloid of One Sheet. 15.7 Divergence Theorem. 15.8 Stokes's Theorem. Section Project: The Planimeter. Bonus Online Material. Chapter 16: Additional Topics in Differential Equations (please visit URL to come). 16.1 Exact First-Order Equations. 16.2 Second-Order Homogeneous Linear Equations. 16.3 Second-Order Nonhomogeneous Linear Equations. Section Project: Parachute Jump. 16.4 Series Solutions of Differential Equations. Book Appendices. A. Proofs of Selected Theorems. B. Integration Tables. Online Appendices. C. Precalculus Review (please visit URL to come). C.1 Real Numbers and the Real Number Line. C.2 The Cartesian Plane. C.3 Review of Trigonometric Functions. D. Rotation and the General Second-Degree Equation (please visit URL to come). E. Complex Numbers (please visit URL to come). F Business and Economic Applications (please visit URL to come).
Includes index.
Keywords: CALCULUS